2005
DOI: 10.1093/annonc/mdi083
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of borderline ovarian tumors: results of a French multicenter study

Abstract: Laparoscopic management of borderline ovarian tumors is associated with a higher rate of cyst rupture and incomplete staging. Recurrence was more frequent after conservative treatment. Whatever the surgical route, the rate of complete initial staging was low, emphasizing the need to respect treatment guidelines for borderline ovarian tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
4
17

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(112 citation statements)
references
References 26 publications
9
82
4
17
Order By: Relevance
“…Using this approach, some borderline ovarian tumors would receive similar treatment to benign lesions with a risk that their content would sometimes be spilled during minimally invasive surgery and that they would not be fully staged. There is no evidence, however, that this would have an adverse effect on long-term outcomes and survival rates 15 . Borderline ovarian tumors tend to occur in young women in whom preservation of fertility is of utmost importance 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, some borderline ovarian tumors would receive similar treatment to benign lesions with a risk that their content would sometimes be spilled during minimally invasive surgery and that they would not be fully staged. There is no evidence, however, that this would have an adverse effect on long-term outcomes and survival rates 15 . Borderline ovarian tumors tend to occur in young women in whom preservation of fertility is of utmost importance 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, one third of borderline ovarian tumors are diagnosed in women younger than 40 years, and more than 80% of cases are detected early in the disease course, raising issues of fertility-sparing surgery, laparoscopic management, and restaging operations (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Accepted As a Distinct Histological Entity By The Internatiomentioning
confidence: 99%
“…There is some evidence in the literature that spillage of invasive epithelial ovarian tumors at surgery may adversely affect patients' long-term outcomes 15 . The prognosis of borderline tumors, particularly those of gastrointestinal type, is very good, and there are no strong data to suggest that the spillage of cyst fluid decreases survival rates 16 , although some studies have shown an increased risk of recurrence 17,18 . Nevertheless, it would be prudent to take measures to minimize the risk of spillage until more evidence is available about its effect on women's health.…”
Section: Discussionmentioning
confidence: 99%